2022
DOI: 10.3389/fonc.2022.848779
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pralsetinib as Neoadjuvant Therapy for Non-Small Cell Lung Cancer Patient With RET Rearrangement

Abstract: RET rearrangements are rare, and occur in 1%-2% of all non-small cell lung cancer (NSCLC) patients. Pralsetinib has a significant anti-tumor effect in patients with advanced NSCLC and a RET rearrangement. Previous studies have confirmed the efficiency of neoadjuvant target therapy for NSCLC. Herein we present a case involving a female patient who was diagnosed with stage IIIA lung adenocarcinoma and harbored a KIF5B-RET rearrangement based on next-generation sequencing. Radiologic downstaging was indicated aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous clinical trials have already verified the availability of EGFR and ALK inhibitors neoadjuvant targeted therapy in the disease control and pathological downstaging for early-stage NSCLC patients harboring the corresponding mutation, and some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK , RET and ROS1 -positive resectable NSCLC patients ( 3 , 6 , 13 15 ). MET ex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients ( 16 ).…”
Section: Discussionmentioning
confidence: 91%
“…Immunohistochemistry outcomes were presented as: HE (A), TTF-1 (+) (B), NapsinA (+) (C), CK7 (+) (D), CK5/6 (-), CK (pan) (+), and Ki-67 (+, about 50%). some case reports also observed that target therapy provided effective radiologic and pathologic response in ALK, RET and ROS1-positive resectable NSCLC patients (3,6,(13)(14)(15). METex14m is an independent oncogenic driver occurring in 2.8% of resected stage I-III NSCLC patients (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfactory effects have been shown in this study, with partial response in eight patients and disease stabilization in another two patients ( 8 ). In addition, pralsetinib was used as neoadjuvant therapy in a case study, in which a 54-year-old female with stage IIIA lung adenocarcinoma achieved apparent radiologic downstaging after pralsetinib therapy for one month, and the mass of primary tumor was reduced by 74% postoperatively ( 9 ). Even though pralsetinib has consistently shown therapeutic benefits in previous studies, its effects on elderly NSCLC patients with RET fusion remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Another mutation that is being explored is a RET mutation in NSCLC patients that have been treated with pralsetinib. Zhou et al [36] reported a patient with resectable Stage IIIA NSCLC with a RET mutation (KIF5B-RET fusion). The patient was treated with neoadjuvant pralsetinib for 4 weeks, showing a 74% response rate post-operatively.…”
Section: Future: Neoadjuvant Targeted Therapymentioning
confidence: 99%